Implementasi Cyber Public Relations dalam Membangun Citra Positif Polres Metro Jakarta Barat pada Sosial Media Instagram @polres_Jakbar - Komalasari, Khoiriyah Nur; Harahap , Halomoan (Innovative: Journal Of Social Science Research, 2025)
Compared to the implementation of Cyber Public Relations on other Metro Police Instagram social media, the implementation of Cyber Public Relations of West Jakarta Metro Police has advantages such as having a Polri TV program on video reels content on Instagram social media @polres_jakbar. Not only that, @polres_jakbar also publishes a lot of information such as police activities and programs, information about missing people, press releases, holiday greetings, quotes or promotions and of course there is educational video content that is attractively packaged in collaboration with several influencers, of course, every content published with infographics that are easy to understand and use supporting visuals, this is in line with the inspirational photography award, viralization and narrative awards to the Public Relations of West Jakarta Metro Police. Qualitative approach with case study research type and descriptive in nature, with data obtained through interviews, observation, and documentation analysis. The results show that the implementation process of Cyber Public Relations of West Jakarta Metro Police on Instagram social media uses the 7C PR program, namely credibility, context, content, clarity, continuity and consistency, channel, and capability of the audience. The implementation of Cyber Public Relations on Instagram has had a positive impact on changing the image of West Jakarta Metro Police.